Local government and prophylaxis HIV/AIDS - Zielazny, Paweł; Karakiewicz, Beata; Rotter, Iwona; Jurczak, Anna (Polish Journal of Public Health, 2012)
In spite of significant medical progress which has been made in HIV virus infection treatment, still the most efficient way of fighting HIV is health prophylaxis combined with education. The preventive measures should be pursued by the government administration but at the same time by local authorities.In Poland health policy regarding HIV/AIDS problems has been poorly implemented by local authorities. The reason for that is among others lack of knowledge of law on HIV/AIDS prophylaxis, lack of understanding of the health needs of local communities as well as the lack of financial resources.The basic role of local authorities on HIV/AIDS should include organising of complex prophylactic actions of medical and social nature. The actions should take into consideration local determinants and include such elements like: permanent monitoring of HIV infections in the local area, prevention of HIV infection spreading by organizing appropriate preventive measures, creation of the local Consulting-Diagnostic Centres where the HIV tests can be made free of charge and anonymously, financial support for non-governmental organizations operating in HIV/AIDS subject.In Poland there are many legal acts that allow developing effectively and realizing the health-oriented actions by local authorities. The basic legal act in this regard is the Ministerial Ordinance of 13 September 2005 on the National Programme for Combating AIDS and HIV Prevention (Official Journal of 30 September 20052). In the Ordinance, in relation to the units of local authorities the detailed definitions of the actions for realization were resigned of, limited to define the main directions of the actions. Local authorities have been left with autonomy in decision making.2 Starting from 1 January 2012 Rozporządzenie Rady Ministrów z dnia 15 lutego 2011 r. w sprawie Krajowego Programu Zapobiegania Zakażeniom HIV i Zwalczania AIDS will be in force.